EFFECT OF PROPOSED TRAINING PROGRAM AGILITY TO DEVELOP THE ACCURACY OF SOME OFFNC SKILLS IN HANDBALL - Drosh, Amar (Journal of Physical Education, 2008)
THE AIM OF THE STUDY WAS TO IPENTIFY THE EFFECT OF PROPOSED TRAINING PROGRAM FOR AGILITY TO DEVELOP THE ACCURACY OF SOME OFFENCE SKILLS IN HANDBALL THE RESEARCMER HYPOTHESISED THAT THERE ARE SIGNIFICANT DIFFERENCES IN OFFENCE SKILLS BETWEEN PRE AND POST TEST . ANOTHER HYPOTHESIS WAS THAT THE PROPOSED TRAINING PROGRAM HAS POSITIVE EFFECT ON AGILITY .44 GOLLEGE STUDENTS SERVED AS ASAMPLE .SAMPLE WAS DEVIDED INTO TWO GROUPS IMENTAL AND CONTROL GROUP . BOTHE GROUPS UNDERWENT THE SAME TESTS . THE RESULTS REVEALED THAT THERE ARE SIGNIFICANT DIFFERENCES BETWEEN GROUPS IN POST TESTS –W AGILITY AND OFFENCE SKILLS . THE STUDY RECOMMANDED USING THIS PROGROM FOR BETTER ACHEIVEMENT IN HANDBALL